2001
DOI: 10.1093/ndt/16.9.1818
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction and the effects of sildenafil treatment in patients on haemodialysis and continuous ambulatory peritoneal dialysis

Abstract: The rate of erectile dysfunction is high in dialysis patients. Penile blood flow is the most important factor for predicting both the development of erectile dysfunction and the response to sildenafil therapy in such patients. Oral sildenafil is an effective, reliable, well-tolerated treatment for uraemic patients with erectile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 17 publications
5
79
0
2
Order By: Relevance
“…Approximately 50% of uremic men complain of erectile dysfunction, while an even greater percentage of both men and women complain of decreased libido and a marked decline in the frequency of intercourse. [1,6] Soykan et al used the Arizona Sexual Experience Scale (ASEX) and reported that sexual dysfunction was 61% in female with HD patients. [5] Basok et al using FSFI scores reported that the rates of FSD were 81, 66.7, and 50% in the PD and HD patients and control subjects, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of uremic men complain of erectile dysfunction, while an even greater percentage of both men and women complain of decreased libido and a marked decline in the frequency of intercourse. [1,6] Soykan et al used the Arizona Sexual Experience Scale (ASEX) and reported that sexual dysfunction was 61% in female with HD patients. [5] Basok et al using FSFI scores reported that the rates of FSD were 81, 66.7, and 50% in the PD and HD patients and control subjects, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 However, in HD patients studies report very high rates of ED of 71-80%. [1][2][3][4][5][6] Compared to non-uremic patients, the high rate of ED in HD patients has been identified as having organic and psychogenic causes. The successful treatment of ED in HD patients increases the quality of life and reduces psychometric factors in the ED etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the prevalence of ED is 71-80% in HD patients. [1][2][3][4][5][6] It has been found that organic and psychogenic factors are involved in severe increases in ED in HD patients compared to non-uremic patients. [7][8][9] In HD patients, there are increases in testicular failure, secondary disturbances in the pituitary-gonadal axis, plasma estrogen, and prolactin levels identified in the early period.…”
Section: Introductionmentioning
confidence: 99%
“…30 In chronic renal failure, 60% of patients with ED have a positive response to 50 or 100 mg of sildenafil. 31 This response rate is observed in both hemodialysis and ambulatory peritoneal dialysis patients. In all, 60% of renal transplant patients with ED who were treated with sildenafil reported an improvement in achieving and maintaining erections.…”
Section: S22mentioning
confidence: 92%